2003
DOI: 10.1002/pits.10096
|View full text |Cite
|
Sign up to set email alerts
|

Developmental, gender, and practical considerations in scoring curriculum‐based measurement writing probes

Abstract: The present study focused on CBM written language procedures by conducting an investigation of the developmental, gender, and practical considerations surrounding three categories of CBM written language scoring indices: production-dependent, production-independent, and accurateproduction. Students in first-through eighth-grade generated a three-minute writing sample in the fall and spring of the school year using standard CBM procedures. The writing samples were scored using all three types of scoring indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 4 publications
12
79
0
3
Order By: Relevance
“…Girls' superior performance on spelling has also been reported before (e.g., Malecki & Jewell, 2003). However, this result should be evaluated cautiously.…”
Section: Language Group and Gender Differences In Written Expressionmentioning
confidence: 73%
See 2 more Smart Citations
“…Girls' superior performance on spelling has also been reported before (e.g., Malecki & Jewell, 2003). However, this result should be evaluated cautiously.…”
Section: Language Group and Gender Differences In Written Expressionmentioning
confidence: 73%
“…6 DIMENSIONS OF WRITTEN EXPRESSION of both compositional fluency and quality. Likewise, Malecki and Jewell (2003) found that girls outperformed boys on all dimensions of written expression including compositional fluency and spelling accuracy among children from early to middle primary grade levels. Trio et al (2012) reported similar gender gaps in favour of girls with children from about 8 to 16 years of age.…”
Section: Dimensions Of Written Expression 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…An increased sample size would also allow additional cognitive measures to be contrasted within the regression analyses, for example the contribution of reading, spelling and vocabulary skills to writing fluency and quality (Sumner et al, 2014). It is also important to extend these findings to consider how the text genre (Beard & Burrell, 2010) and assessment metrics applied (Berninger, Whitaker, et al, 1996;Malecki & Jewell, 2003) may affect the conclusions drawn about the relative skills of boys and girls.…”
Section: Limitationsmentioning
confidence: 99%
“…Deney ve kontrol grupları arasında yazma başarısı açısından anlamlı bir fark olmaması, yazma başarısının artmasında belli stratejilerin izlendiği geleneksel öğretimin de etkili olabileceğini düşündürebilir. Zaten bu araştırmada olduğu gibi diğer araştırmalarda da (Bui, Schumaker, & Deshler, 2006;Graham & Harris, 2005;Graham & Perrin, 2006;Malecki & Jewell, 2003) geleneksel öğretimin yazma başarısını artırdığı sonucuna ulaşılmıştır.…”
Section: Sonuç Ve Tartışmaunclassified